Modeling Terrorists. - Ackerman, G. (IEEE spectrum)
This paper describes the ongoing research within the US intelligence community on the use of simulators to gain vital insights into the minds and motives of terrorists and the structure and critical links in their organizations. Different forms of software are aimed at military officials, who are already using such programs to train officers and troops, and at intelligence analysts, who are finding that the shadowy, shifting organizations they must study are so complex and unstable that keeping track of all the variables without computer help is increasingly unrealistic. Critics, however, feel that human behavior modeling does not necessarily contribute to truly understanding the reasons that motivate an individual's behavior. For them, modeling allows, and maybe even encourages, people to avoid considering the legitimacy of certain grievances that drive terrorist behavior